Case Study: Green Event Through the Use of Renewable Energy in Organizing the Get the Fest 2022 Event - HENDRATMO, Cestia Astutiningsih; LEMY, Diena Mutiara; KUSUMO, H.K. Elang (Journal of Tourism Economics and Policy, 2024)
Events as a catalyst for the revival of tourism after the pandemic are the focus issues in event development in Indonesia. Events are one of the typical tourism activities with a "life experience" that provides a complete experience to tourists who travel with special motivation. The event itself is a sector that is able to provide economic growth and multiplier effect such as job opportunities, improving destination image and growing regional income. However, along with the growth in the level of event organization, negative impacts are also visible, especially on the environmental sector. This research aims to further examine the concept of green event in Get the Fest activities, the extent to which this event can apply the concept, and what are the benefits that can be felt directly or indirectly by the event participants themselves. This research uses a descriptive qualitative method by describing a phenomenon in detail and presenting the data found in detail. The study found that event organizers are starting to take a more environmentally friendly approach by using the green event concept. However, as an emerging trend, the concept of Green Event is wide with different methods of application. The case studied in this research that held in early 2024 is the implementation of green event at the "Get the Fest" event which implements environmentally friendly events through the use of renewable energy.